Функції діалогу й авторської ремарки в жанрі німецькомовної драми ХХ ст. - Горюнова, Марина Миколаївна; Goriunova, M. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Досліджено особливості функцій діалогу й авторської ремарки на основі аналізу стильової специфіки мови драматургії ХХ ст. У статті здійснено спробу висвітлити, що дієва функція мови драми залежить від по¬зиції автора в художньому тексті, а синтез саме діалогу й авторського мовлення в текстовому полі породжує не тільки нові функції драматургічного діалогу, а й жанрову своєрідність німецькомовної драми зазначеного періоду. The research of the dialogue and author’s remark function peculiarities has been done based on the style specific character analysis in the play writing language of the 20th century, proceeding from the suggestion that the artistic work is the result of the selective means synthesis both at the linguistic and the extra-linguistic levels. The attempt has been made in the paper to show that the efficacious function of drama language depends upon the author’s position regarding fiction text, and the dialogue and author’s speech synthesis in the text field gives birth not only to the dramatic dialogue new functions, but also to the German-speaking drama of the above period of time genre peculiarity.
The Dialogue and Author’s Remark Functions in the Genre of German-Speaking Drama of the 20th Century
Keywords: драма; drama; діалог; dialogue; авторська ремарка; author’s remark